(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: The acute shortage of human donor corneas for transplantation has emerged, setting ophthalmologists a task of searching for new graft materials for use in keratoplasty. Purpose: To investigate the possibility of using the keratoxenoimplant for therapeutic or therapeutic-and-tectonic keratoplasty in ocular burns or ulcerative sequelae of corneal inflammatory diseases. Materials and Methods: A clinical study of the use of the keratoxenoimplant was performed in 69 eyes (60 patients) with ocular burns or ulcerative sequelae of corneal inflammatory diseases. Results: In all eyes of the study, the keratoxenoimplant was found to facilitate the preservation of the globe and light perception. In some patients, following a number of rehabilitative-and-reconstructive procedures, we managed to implant the keratoprosthesis and to restore sight (in some cases to the visual acuity of 0.5). Conclusion: The results provide the basis for recommendation of the keratoxenoimplant for wide use if human donor material is not easily available.